Effects of shear rate and forced convection residence time on asymmetric polysulfone membranes structure and gas separation performance - Ismail, A. F.; Ng, B. C.; Abdul Rahman, W. A. W. (Elsevier, 2003)
The objectives of this study are to illustrate the effects of shear rate and forced convection residence time on asymmetric polysulfone membrane structure and gas separation performance. The membranes were produced by a simple dry/wet phase inversion technique using a pneumatically-controlled flat sheet membrane casting system. Varying the casting speed varied shear rate. Rheologically induced molecular orientation in membranes during casting was measured directly using plane polarized reflectance infrared spectroscopy technique. The highly sheared asymmetric membranes tend to exhibit greater molecular orientation in the skin layer. Thus, a high pressure-normalized flux and selectivity were obtained. The mean pressure-normalized fluxes of O2 and CO2 were about 5.05 and 11.41 GPU, respectively. The selectivity of O2/N2 and CO2/CH4 were approximately 6.72 and 32.63, respectively, at shear rate of 367 s1. However, increasing forced convection residence time in the dry phase inversion step resulted in lower pressurenormalized flux but higher selectivity membrane. The best membrane performance obtained based on the trade-off between pressure-normalized flux and selectivity was observed at forced convection residence time of 20 s and at 367 s1 shear rate.